Analyzing the Student’s Phonological Awareness and its Relation to the Reading Skill in EFL Classroom - Susanto, Susanto; Nanda, Deri Sis (Jurnal Ilmiah Peuradeun, 2023)
Phonological awareness has been claimed as one of the significant factors in learning to read. This paper reported our research on students' phonological awareness in EFL classrooms. We wanted to examine whether the phonological awareness tasks correlate with reading accuracy. Firstly, we analyzed their phonological awareness in the tasks of identification, substitution, addition, and deletion in English phonemes and syllables. Then, we discussed the relationship between phonological awareness and reading skills. We observed the students (N=143) of the even semesters (II, IV, VI, and VIII) at the English Education Department (Academic Year 2021/2022), Universitas Bandar Lampung, Indonesia. From the complete task of knowing students' phonological awareness that has been carried out, there was an increase in the average score from Semester II to Semester VIII students. The highest mean score was found in the student's test scores of Semester VIII (91.2; SD 6.3) and the lowest for Semester II students (62.5; SD 11.4). To test whether the phonological awareness tasks correlated with reading accuracy, the Pearson product-moment correlation coefficient (r) was calculated, and the results showed that the reading accuracy had a positive correlation either for the phoneme (r = 0.472) and syllable (r = 0.534) tasks and the correlation was significant (p < .01).